Cardiorenal Syndrome Type 5: In Vitro Cytotoxicity Effects on Renal Tubular Cells and Inflammatory Profile - Alessandra Brocca; Grazia Maria Virzì; Chiara Pasqualin; Silvia Pastori; Stefano Marcante; Massimo de Cal; Claudio Ronco (Analytical Cellular Pathology)
Background. Cardiorenal Syndrome Type 5 (CRS Type 5) reflects concomitant cardiac and renal dysfunctions in the setting of a wide spectrum of systemic disorders. Our aim was to study in vitro effects of CRS Type 5 plasma on renal tubular cells (RTCs), in terms of cellular death and the characterization of inflammatory plasma profile in these patients. Material and Methods. We enrolled 11 CRS Type 5 patients from ICU and 16 healthy controls. Plasma from patients and controls was incubated with renal tubular cells (RTCs) and cell death was evaluated. Plasma cytokines were detected. Results. RTCs incubated with CRS Type 5 plasma showed significantly higher apoptosis and necrosis with respect to controls. Plasma cytokine profile of CRS Type 5 patients was significantly different from controls: we observed the production of pro- and anti-inflammatory mediators in these patients. Caspase-3, caspase-8, and caspase-9 were activated in cells treated with CRS Type 5 plasma compared to controls. Conclusions. Our results underline the cytotoxic effect of CRS Type 5 mediators on RTC viability, probably due to the activation of both intrinsic and extrinsic pathways of apoptosis and to the deregulation of cytokine release. The consequence may be the damage of distant organs which lead to the worsening of condition of patients.